2019
DOI: 10.1111/hdi.12733
|View full text |Cite
|
Sign up to set email alerts
|

Early use of PEPA dialyzer for light chains removal and for the recovery from myeloma cast nephropathy: A case report

Abstract: Chemotherapy and extracorporeal treatment reduce serum free light chains (FLCs) allowing the recovery of acute kidney injury (AKI) caused by myeloma cast nephropathy (MCN). We report the first case of recovery from AKI in a patient with MCN who underwent the removal of FLCs using the PEPA filter, with an undisclosed cut‐off, combined with chemotherapy for multiple myeloma (MM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In consideration of our previous positive experience in a single case report and in a cohort of 16 patients, in our patient 2 PEPA dialyzers were used in series during each HDF session with positive outcome and without albumin loss [ 37 , 38 ].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In consideration of our previous positive experience in a single case report and in a cohort of 16 patients, in our patient 2 PEPA dialyzers were used in series during each HDF session with positive outcome and without albumin loss [ 37 , 38 ].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…14 In 2023, a study of eight patients 17 with a 269min session length and Qb between 313 and 330 mL/ min, showed that removal of β 2 -microglobulin, κFLC, and λFLC RRs were similar between FDY 210 in HD, Theranova 500 in HD, Vie 21X in HD, all three MCO dialyzers, versus Elisio 21H in post-dilution HDF, and all of them were superior to Elisio 21H in HD. In 2019, Donati et al 18 published a case report of recovery from acute kidney injury secondary to λFLC myeloma cast nephropathy with the FDY 210 dialyzer combined with bortezomib chemotherapy in seven HD treatments, with λFLC RRs ranging between 40% and 70%. In this study, all HD and HDF treatments showed good safety, with a global blood albumin RR.…”
Section: Discussionmentioning
confidence: 99%
“…As to PEPA dialyzer, our group published the first successful case report of a patient affected by AKI due to MCN who experienced the recovery of renal function by means of chemotherapy combined to extracorporeal removal of sFLC. Two PEPA dialyzers were used in series during the 7 dialysis sessions carried out for sFLC removal [17]. There are no other in vivo experiences of removal of sFLC with PEPA dialyzer.…”
Section: Discussionmentioning
confidence: 99%